Trajectory Perception and Object Continuity: Effects of Shape and Color Change on 4-Month-Olds’ Perception of Object Identity - Bremner, J. Gavin (2012)
Previous work has demonstrated that infants use object trajectory continuity as a cue to the constant identity of an object, but results are equivocal regarding the role of object features, with some work suggesting that a change in the appearance of an object does not cue a change in identity. In an experiment involving 72 participants, we investigated the effects of changing object shape and color, singly and in combination, on 4-month-olds’ perception of object continuity. A change in the shape of an object while it passed behind an occluder had no effect on perception of continuity, whereas a change in shape and color led to perception of discontinuity, and a change in color led to no clear percept regarding continuity or discontinuity. These results are discussed in terms of a perceptual learning model of development of object identity.